Review: Genetic Improvement in Livestock: A Journey from Conventional Breeding to Genomic Precision - Kaleem Ullah; Abdul Waheed (Veterinary Biomedical and Clinical Journal, 2025)
From conventional breeding techniques to the advent of genomic precision, the practice of genetically altering livestock has experienced a substantial change over the last century. Conventional breeding methods like selective breeding, crossbreeding and artificial insemination (AI) have long served as the foundation for livestock development. Even though these techniques were successful, they were unable to fully address complex genetic factors as such techniques were primarily reliant on phenotypic selection and observable traits. Although early crossbreeding innovations aimed to enhance performance by utilizing hybrid vigor meanwhile, artificial insemination made it possible for breeders to use superior sire genetics more widely. The development of molecular genetics in the latter half of the 20th century, especially marker-assisted selection (MAS), revolutionized breeding practices by increasing the accuracy of selection for hard-to-measure traits like disease resistance. It accelerated the advancement of genetics by enabling breeders to more rapidly identify individuals with superior genetic makeup. Using high-density genotyping and genomic estimated breeding values (GEBVs), genomic selection was introduced in the early 21st century to more precisely assess genetic potential particularly for complex traits. Then more advanced innovations such as next-generation sequencing (NGS), whole genome sequencing (WGS) and clustered regularly interspaced short palindromic repeats (CRISPR) further aided the genetic improvement process. By combining genomics, big data analytics and artificial intelligence (AI); livestock breeding is progressing and precision livestock farming (PLF) is being promoted. This review examines the development of livestock genetics enhancement following the path from early conventional breeding techniques to the ground-breaking impacts of genomic precision.